2011
DOI: 10.1186/1471-244x-11-131
|View full text |Cite
|
Sign up to set email alerts
|

Meta-review of the effectiveness of computerised CBT in treating depression

Abstract: Background: Several computerised cognitive behaviour therapy (cCBT) packages are now available to treat mild to moderate depression with or without anxiety. These have been usually been reviewed alongside cCBT for a wide range of psychological problems. Here, we single out the results of these reviews for the most common mental disorder, mild to moderate depression. The aim of this paper is to evaluate the quality of existing reviews and to enable reliable comparisons of alternative computer packages for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 21 publications
2
92
0
2
Order By: Relevance
“…140 In efforts to avoid duplication of work, and to ensure that limited resources were used to maximum effect, the review team decided not to progress any further with the quantitative review of depression self-management support.…”
mentioning
confidence: 99%
“…140 In efforts to avoid duplication of work, and to ensure that limited resources were used to maximum effect, the review team decided not to progress any further with the quantitative review of depression self-management support.…”
mentioning
confidence: 99%
“…Among these, we can highlight the well-documented cognitive-behavioral therapy (CBT) 38,39 and positive psychotherapy. 40,41 CBT is a widely researched form of psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Before we summarize the findings concerning t h e e f f i c a c y o f c C B T w e w o u l d l i k e t o mention that computers and the internet can not only be used as an alternative to the traditional form of CBT but also as an adjunct to the individual contact with a therapist [78]: For example a computer can be used as a tool for screening or diagnosis and information can be provided either in written or in audio/video formats. Furthermore, structured selfhelp programs can be provided online whereby situations can be easily simulated and graded exposure in highly controlled conditions is possible.…”
Section: New Developments In the Cbt For Depressionmentioning
confidence: 99%
“…Besides the easy accessibility and the potential to offer an approach in a nonstigmatizing environment there are some further advantages in conducting computerized CBT (cCBT). For instance, cCBT has the capacity to deliver structured input consistently with precision and is associated with comparably low costs [78]. Moreover, it has been shown that discontinuation of treatment is a problem that seems to be associated with faceto-face therapy [79].…”
Section: New Developments In the Cbt For Depressionmentioning
confidence: 99%
See 1 more Smart Citation